Cinnamaldehyde and α-terpineol as an alternative for using as denture cleansers: antifungal activity and acrylic resin color stability (Research, Society and Development, 2021)
Objective: here was investigated the potential of phytoconstituents as cinnamaldehyde and α-terpineol as denture cleansers, which was evaluated the antifungal activity, also their effect on the color change of the poly(methyl)methacrylate (PMMA). Methodology: Candida albicans biofilms were formed on PMMA specimens and exposed a 10 minutes daily treatment with cinnamaldehyde (10 mg/ mL), α-terpineol (10 mg/ mL), NaCl 0.9%, and NaClO 1%. Biofilms were collected, then analyzed the cell viability (CFU/ mL), cell metabolism (MTT), and roughness. Moreover, the color variation of the specimens during seven and 14 days was checked. Kruskal-Wallis, Mann Whitney, and ANOVA one-way were applied (α < 0.05). Results: cinnamaldehyde and α-terpineol decrease the number of viable cells compared to NaCl 0.9% by 76% and 83.2%, respectively (p< 0.05). Both substances reduce biofilm metabolism by around 70% (p< 0.05). Also, the phytoconstituents showed low biofilm roughness, similar to NaClO (p> 0.05), without changing the color of the acrylic resin (p> 0.05). Conclusion: cinnamaldehyde and α-terpineol, at a concentration of 10 mg/ mL, shows antifungal activity on C. albicans biofilms free from PMMA surface changes. From a clinical viewpoint, these substances have a strong potential to be incorporated into denture cleansers solutions.